ANALISA YURIDIS PERTANGGUNG JAWABAN PIDANA LAKA LANTAS TUNGGAL YANG MENGAKIBATKAN HILANGNYA NYAWA ORANG LAIN (STUDI DI POLRES BATUBARA) - Doni Irawan Harahap; Alpi Sahari (JURNAL DOKTRIN REVIEW, 2022)
Road traffic and transportation are important in increasing social mobility for the people of Indonesia because all the time Indonesian people continue to be attached to various kinds of interests in the use of transportation. The Indonesian people must follow and comply with all traffic rules regulated by Law no. 22 of 2009 concerning Road Traffic and Transportation (UULDAJ). Road users often ignore traffic signs. UULDAJ contains sanctions for traffic violations and regulates matters regarding traffic crimes. Criminal provisions start from Article 273 to Article 317. Traffic accident is an incident on the road that is unexpected and unintentional involving a vehicle with or without other road users resulting in human casualties and/or property loss. A single accident is an accident that only involves one motor vehicle and does not involve other road users at all. Negligence in traffic that results in traffic accidents causing vehicle damage, causing injuries, and even death to other people is regulated in Article 310 of the UULLDAJ which determines criminal liability for anyone driving a motorized vehicle due to negligence resulting in traffic accidents with serious injuries to the victim shall be punished with imprisonment. maximum 5 years. Meanwhile, in the event of an accident that results in the death of another person, the punishment is a maximum imprisonment of 6 years. The Police Institution related to the Coal Police Station is the implementer of the duties and authorities of the National Police in the city district area. In connection with the event of an accident, the Police officer is obliged to handle the accident by going to the scene of the incident immediately, helping the victim, processing the scene of the case, regulating the smooth flow of traffic.